Bianchi Type-I Universe with Cosmological Constant and Quadratic Equation of State in f(R,T) Modified Gravity - G. P. Singh; Binaya K. Bishi (Advances in High Energy Physics)
This paper deals with the study of Bianchi type-I universe in the context of f(R,T) gravity. Einstein’s field equations in f(R,T) gravity have been solved in the presence of cosmological constant Λ and quadratic equation of state (EoS) p=αρ2-ρ, where α≠0 is a constant. Here, we have discussed two classes of f(R,T) gravity; that is, f(R,T)=R+2f(T) and f(R,T)=f1(R)+f2(T). A set of models has been taken into consideration based on the plausible relation. Also, we have studied some physical and kinematical properties of the models.